2010
DOI: 10.1177/194008291000300404
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Attributes Drive Complex Spatial Microclimate Configuration of Brazilian Atlantic Forest Fragments

Abstract: Habitat fragmentation imposes profound impacts on the tropical forest microclimate, but the microclimatic configuration of isolated forest patches and its implications for biodiversity persistence and habitat management are not clear. In this study we assessed a set of 10 aged (> 80 years) fragments (3.0 -3,500 ha in size) of the Atlantic forest to examine to what extent fragment microclimatic attributes are correlated with distance to the nearest edge as frequently proposed in the literature. We used 129 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 48 publications
(76 reference statements)
2
34
0
1
Order By: Relevance
“…Habitat connectivity can positively affect plant species richness, for example by increasing seed dispersal, facilitating pollen movement, and altering foraging (Tewksbury et al 2002), even in areas with seemingly small distances of isolation between patches. Damschen et al (2006) found a net positive effect on native plant species richness in patches connected by corridors, compared to patches isolated by 150 m. Additionally, surrounding forests may have the potential to buffer existing forest fragments from microclimatic edge effects; in tropical forests, landscape level influences such as increasing forest cover and structural connectivity influenced microclimatic differences between forest fragments and the surrounding matrix, with air temperature and moisture in larger and more connected fragments deviating less from the surrounding matrix (Pinto et al 2010). However, the majority of forest fragmentation studies focus primarily on summary metrics such as species richness and composition (Estades and Temple 1999, Honnay et al 1999, Petit et al 2004, Uezu et al 2005, Damschen et al 2006, Echeverría et al 2007, and dispersal of organisms (Tewksbury et al 2002, McEuen and Curran 2004, Kolb and Diekmann 2005, Pardini et al 2005, and rarely make the link to ecosystem functions or services (but see Billings and Gaydess 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat connectivity can positively affect plant species richness, for example by increasing seed dispersal, facilitating pollen movement, and altering foraging (Tewksbury et al 2002), even in areas with seemingly small distances of isolation between patches. Damschen et al (2006) found a net positive effect on native plant species richness in patches connected by corridors, compared to patches isolated by 150 m. Additionally, surrounding forests may have the potential to buffer existing forest fragments from microclimatic edge effects; in tropical forests, landscape level influences such as increasing forest cover and structural connectivity influenced microclimatic differences between forest fragments and the surrounding matrix, with air temperature and moisture in larger and more connected fragments deviating less from the surrounding matrix (Pinto et al 2010). However, the majority of forest fragmentation studies focus primarily on summary metrics such as species richness and composition (Estades and Temple 1999, Honnay et al 1999, Petit et al 2004, Uezu et al 2005, Damschen et al 2006, Echeverría et al 2007, and dispersal of organisms (Tewksbury et al 2002, McEuen and Curran 2004, Kolb and Diekmann 2005, Pardini et al 2005, and rarely make the link to ecosystem functions or services (but see Billings and Gaydess 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as latitude, vegetation cover, elevation, and distance from the coastline all create substantial spatial variation in climate (e.g., Shoo et al, 2010Shoo et al, , 2011. Indeed, microclimate may differ over even very small landscape scales (e.g., Pinto et al, 2010). For all of these reasons, isolates at the geographic edge of a species' range will likely experience a different climate (both in mean and extreme values) from the climate at the center of the species' range (Lesica and Allendorf, 1995).…”
Section: Climatic Environmentmentioning
confidence: 99%
“…It 1 is important to note that due to the favorable fragment shape and size, several fragment plots were located inside the >200 m 2 range. However, due to the complexities of edge penetration by microclimatic effects (Pinto et al, 2010) and isolation, these 3 samples were still statistically considered as fragments, and not core areas (Melo et al, 2006;Santos et al, 2008;Tabarelli 4 and Lopes, 2008). To illustrate this, we separated the small fragment plots into edges and core, with the same criteria 5 as used for the large fragment Coimbra (200 m edge) and compared the biomass values (Fig.…”
mentioning
confidence: 99%
“…This is allowed for a more realistic reproduction of the temporal behavior 14 of the model in relation to stem number and biomass changes. Using this core of large forest fragment parameterization, we 15 modified the mortality and establishment parameters and executed simulations with FORMIND, seeking to reproduce edge 16 of large fragment and small fragment stem number and biomass field conditions. These two parameters are considered To simulate changes in forest hydrology, we used FORMIND's climate module, and parameterized it with daily precipitation and potential evapotranspiration from historic averages measured around 60 km from the Serra Grande landscape, Evapotranspiration and total runoff for each patch are calculated based primarily on daily precipitation, potential 35 evapotranspiration, forest structure and soil characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation